Dual Home and Dual Exile of Jan Čep? - Novotný, Vladimír (Bohemica Olomucensia, 2015)
One of the basic categories which are applied on the interpretation of Jan Čep's work is the author's own credo called "dioecy", i.e., the concept of dual home, mostly differentiated as a notion of an inner and outer home. These notions acquire additional meanings particularly with a consideration of Čep's life experience, of his exile, and especially of his reflections about a true homeland or a "second homeland", however, these notions are essential in terms of reflecting his indigenous pilgrimage. Čep has developed this life-time and creative philosophy in his literary journalism and essays, most significantly in his late essayistic exile memoirs Sestra úzkost.
Keywords: Prose works by Jan Čep; dioecy; dual home; second homeland; exile